2009
DOI: 10.1097/md.0b013e3181c2af86
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Serologic Baseline and Follow-Up Features of Syphilis According to HIV Status in the Post-HAART Era

Abstract: There is a lack of large studies appraising the effect of the human immunodeficiency virus (HIV) on the course of syphilis since the advent of highly active antiretroviral therapy (HAART). We aimed to appraise the effect of HIV on clinical and serologic features of syphilis at baseline and during follow-up in the post-HAART era.We designed a retrospective cohort study of consecutive syphilis cases, diagnosed between 2000 and 2007, in an academic venereal disease center. Data were collected using standardized m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
4
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 38 publications
5
21
4
4
Order By: Relevance
“…The data from 2 observational cohorts in Africa suggest that HIV-infected and HIV-uninfected persons responded similarly to therapy [21]. A retrospective study by Farhi et al that compared HIV-infected and -uninfected persons with early syphilis found similar responses to therapy in both groups [26]. A meta-analysis by Blank et al confirmed what was suspected: Data quality for treatment studies among HIV-infected persons is poor [24].…”
Section: Discussionsupporting
confidence: 65%
“…The data from 2 observational cohorts in Africa suggest that HIV-infected and HIV-uninfected persons responded similarly to therapy [21]. A retrospective study by Farhi et al that compared HIV-infected and -uninfected persons with early syphilis found similar responses to therapy in both groups [26]. A meta-analysis by Blank et al confirmed what was suspected: Data quality for treatment studies among HIV-infected persons is poor [24].…”
Section: Discussionsupporting
confidence: 65%
“…Although studies exist which indicate that the clinical course of syphilis is not significantly distinct between HIV-infected and -uninfected individuals, 36,37 our findings of increased numbers of T. pallidum in lesions of HIV ϩ patients would suggest that the antisyphilitic immune response in these individuals is not very effective, and certainly not protective. It therefore appears that IFN-␥/IL-17-double-positive CD8 ϩ T-cells and macrophages are perhaps needed but do not suffice to eliminate T. pallidum.…”
Section: Discussioncontrasting
confidence: 41%
“…Osutka przebiega zazwyczaj bez świądu (jest plamista 2-3 miesiące od powstania owrzodzenia, następnie grudkowa), zmiany skórnośluzówkowe występują u 90% pacjentów. Może pojawić się podwyższona ciepłota ciała, uogólniona limfadenopatia, zapalenie wątroby, powiększenie śledziony, zapalenie okostnej, zapalenie stawów i zapalenie kłębusz-ków nerkowych [7][8][9][10][11]. Może dojść do zapalenia opon mózgowordzeniowych, porażenia nerwów czaszkowych, zaburzeń dotyczących narządu słu-chu lub wzroku (zapalenia naczyniówki, siatkówki, zapalenia ucha, poszerzenia źrenic), zmian mózgo-wonaczyniowych (udar, zapalenie rdzenia kręgo-wego).…”
Section: Diagnostyka Obraz Klinicznyunclassified